Pengaruh Suku Bunga Kredit dan Kinerja Keuangan Terhadap Harga Saham Pada Sektor Perbankan - Benjamin Agustinus Haloho; Mega Metalia; Agus Zahron Idris; Agrianti Komalasari (Akuntansi, 2024)
Increasing stock trading in Indonesia from year to year increased rapidly. This study serves as an initial investigation of how stock exchange involved in banking services were related to stock prices. This cross-national study utilizes the 2018-2021 financial report. Although this dataset heavily relies on Indonesia Stock Exchange reports, our analysis was guided by signalling theory that recognize the importance of investment and return in mitigating the fraud of banking sectors. Linear regression was conducted to determine factors associated with credit interest rate, performance and stock price. Findings indicate that banks categorized by Financial Service Authority showing prevention progress, have a lower likehood of fraud.